Adaptive Modeling of District Heating Network - Šípal, J. (Elektronika ir Elektrotechnika, 2009)
The article describes the usage of adaptive mathematical model for prediction of the consumption in the system of centralised delivery of heat. This model is possible to use as the useful tool for the generating units operation planning and scheduling. It is the application of the methods of theoretical informatics in the industrial practice, namely at time the method is tested on district heating network in Ústí nad Labem thanks to the close cooperation between the Jan Evangelisty Purkyně University and the heating station Dalkia ČR division Ústí nad Labem. Ill. 7, bibl. 5 (in English; abstracts in English, Russian and Lithuanian).